2007
DOI: 10.1099/mic.0.2006/000372-0
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of a non-virulent mutant of the phytopathogenic bacterium Erwinia chrysanthemi deficient in osmoregulated periplasmic glucans: change in protein expression is not restricted to the envelope, but affects general metabolism

Abstract: Osmoregulated periplasmic glucans (OPGs) are general constituents of the envelope of Gram-negative bacteria. They are required for full virulence of bacterial phytopathogens such as Pseudomonas syringae, Xanthomonas campestris and Erwinia chrysanthemi. E. chrysanthemi is a pectinolytic c-proteobacterium that causes soft rot disease on a wide range of plant species. In addition to the loss of virulence, opg mutants exhibit a pleiotropic phenotype that affects motility, bile-salt resistance, exoenzyme secretion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…(37,38), reduce flagella assembly, and increase sensitivity to antibiotics and detergents (in Rhizobium and Agrobacterium sp and P. aeruginosa) (4,39,40), and to have pleiotropic effects on polysaccharide biosynthesis, protein folding and degradation, and carbohydrate catabolism (in Erwinia chrysanthemi) (41). Loss of periplasmic glucan production in R. meliloti and Bradyrhizobium japonicum affected growth in various hypoosmotic environments (42,43), whereas the opposite effect, decreased growth rates in a hyperosmotic high sodium chloride environment was observed for the C. jejuni pglB, pglE, and pglF mutants where no detectable fOS was present.…”
Section: Discussionmentioning
confidence: 99%
“…(37,38), reduce flagella assembly, and increase sensitivity to antibiotics and detergents (in Rhizobium and Agrobacterium sp and P. aeruginosa) (4,39,40), and to have pleiotropic effects on polysaccharide biosynthesis, protein folding and degradation, and carbohydrate catabolism (in Erwinia chrysanthemi) (41). Loss of periplasmic glucan production in R. meliloti and Bradyrhizobium japonicum affected growth in various hypoosmotic environments (42,43), whereas the opposite effect, decreased growth rates in a hyperosmotic high sodium chloride environment was observed for the C. jejuni pglB, pglE, and pglF mutants where no detectable fOS was present.…”
Section: Discussionmentioning
confidence: 99%
“…The extracytoplasmic stress may be of various types and may involve signal transduction pathways such as RpoE, CpxAR, BaeRS, Rcs (phosphorelays), or PSP (phage shock response) (43,57,58,60,61). In fact, activation of both the RpoE and Rcs phosphorelay systems has been observed in rfa mutants as well as in MDO-, SurA-, and Tol-deficient strains (8,12,19,43,52,78), and induction of oxidative stress has been reported for waaL mutants (5). In addition, inactivation of SurA, a periplasmic chaperone required for outer membrane protein biogenesis (67), results in increased sensitivity to iron (72), again suggesting that cell envelope perturbation leads to oxidative stress.…”
Section: Vol 191 2009 T2s System Iron Homeostasis and Stress Respmentioning
confidence: 99%
“…Second, in E. coli, it was shown that closing of the tricarboxylic acid (TCA) cycle generated ROS synthesis within bacteria, thus inducing the ROS stress response (Kohanski et al, 2008), and in a previous proteomic analysis (Bouchart et al, 2007), it was shown that in an opgG strain, increasing energy level was required as compared with a wild-type strain and resulted in a closed TCA cycle. To test these hypotheses, an opgG eps double mutant strain was constructed by transduction.…”
Section: Motility Is Not Restored In the Opgg Pecs Double Mutant Strainmentioning
confidence: 99%
“…In D. dadantii, mutants devoid of OPGs show a pleiotropic phenotype including a loss of motility, decreased synthesis and secretion of PCWDEs linked to reduced synthesis of the Out system, increased synthesis of exopolysaccharide, induction of a general stress response and complete loss of virulence on potato tubers or chicory leaves (Bouchart et al, 2007;Page et al, 2001). In strains of D. dadantii devoid of OPGs, inactivation of the RcsCDB phosphorelay regulatory system restored PCWDE synthesis and secretion, motility, normal exopolysaccharide synthesis and virulence in potato tubers, indicating that OPGs control the activation level of this phosphorelay (Bontemps-Gallo et al, 2013;Bouchart et al, 2010).…”
Section: Introductionmentioning
confidence: 99%